Effect of environmental aging on the numerical response of FRP-strengthened masonry walls - Ghiassi, Bahman (2016)
Recent durability studies have shown the susceptibility of bond in fiber-reinforced polymer (FRP) strengthened masonry components to hygrothermal exposures. However, it is not clear how this local material degradation affects the global behavior of FRP-strengthened masonry structures. This study addresses this issue by numerically investigating the nonlinear behavior of FRP-masonry walls after aging in two different environmental conditions. A numerical modeling strategy is adopted and validated with existing experimental tests on FRP-strengthened masonry panels. The model, once validated, is used for modeling of four hypothetical FRP-strengthened masonry walls with different boundary conditions, strengthening schemes, and reinforcement ratios. The nonlinear behavior of the walls is then simulated before and after aging in two different environmental conditions. The degradation data are taken from previous accelerated aging tests. The changes in the failure mode and nonlinear response of the walls after aging are presented and discussed.